Perspectives of artist–practitioners on the communication of climate change in the Pacific. Issue 2 (19th December 2017) - Capstick, Stuart; Hemstock, Sarah; Senikula, Ruci
Abstract : Purpose: This study aims to investigate the role of the visual arts for communicating climate change in the context of the Pacific islands, through the perspectives of artists and climate change practitioners. Design/methodology/approach: As part of an "Eco Arts" project carried out in Fiji, semi-structured research interviews were undertaken with artists and climate change practitioners. Findings: Participants' motivations to produce art reflected their personal concerns about, and experiences of, climate change. There was an intention to use art-based approaches to raise awareness and promote action on climate change. The artwork produced drew on metaphors and storytelling to convey future climate impacts and aspects of climate change relevant to Fijian and Pacific communities. Research limitations/implications: The study reports the perspectives of participants and discusses the potential uses of arts communication. Conclusions cannot be drawn from the findings regarding the effectiveness of specific artwork or of arts communication as a general approach. Practical implications: The research offers suggestions for the inclusion of creative approaches to climate change communication within education and vocational training. A consideration of the perspectives of artist–practitioners has implications for the design and conduct of climate change communication. Social implications: The involvement of artist–practitioners in the communication of climate change offers the potential for novel discussions and interpretations of climate change with individuals and within communities, which complement more formal or scientific communication. Originality/value: The present study identifies the motivations and objectives of artist–practitioners involved in climate change communication. The authors highlight the role of personal experience and their use of artistic concepts and creative considerations pertinent to the geography and culture of the Pacific region.